2004
DOI: 10.1016/j.fluid.2004.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Structural effects of small molecules on phospholipid bilayers investigated by molecular simulations

Abstract: We summarize and compare recent Molecular Dynamics simulations on the interactions of dipalmitoylphosphatidylcholine (DPPC) bilayers in the liquid crystalline phase with a number of small molecules including trehalose, a disaccharide of glucose, alcohols, and dimethylsulfoxide (DMSO). The sugar molecules tend to stabilize the structure of the bilayer as they bridge adjacent lipid headgroups. They do not strongly change the structure of the bilayer. Alcohols and DMSO destabilize the bilayer as they increase its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
26
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 56 publications
8
26
1
Order By: Relevance
“…The results shown that ethanol interacts with a POPC membrane primarily via hydrophilic interactions, in particular due to the formation of hydrogen-bonds to the lipid phosphate group. A recent MD investigation has also supported these results and shows that shortchain alcohols exhibit some preference to occupy regions near the upper part of the lipid acyl chains and the phosphatidylcholine headgroups [33,34,61,62]. Additionally, it has been shown that, in a homologous series of aliphatic n-alcohols with an intermediate chain length, an increase in the number of carbon atoms of an alkyl chain (butanol, pentanol and hexanol) results in a gradual decrease in hydrophilic solute-membrane interactions, so that a partitioning process and packing of solute molecules in alcohol/membrane/water systems are driven mainly by hydrophobic forces [63,64].…”
Section: Simulations Of Ternary Cp/membrane/water Systemsmentioning
confidence: 63%
“…The results shown that ethanol interacts with a POPC membrane primarily via hydrophilic interactions, in particular due to the formation of hydrogen-bonds to the lipid phosphate group. A recent MD investigation has also supported these results and shows that shortchain alcohols exhibit some preference to occupy regions near the upper part of the lipid acyl chains and the phosphatidylcholine headgroups [33,34,61,62]. Additionally, it has been shown that, in a homologous series of aliphatic n-alcohols with an intermediate chain length, an increase in the number of carbon atoms of an alkyl chain (butanol, pentanol and hexanol) results in a gradual decrease in hydrophilic solute-membrane interactions, so that a partitioning process and packing of solute molecules in alcohol/membrane/water systems are driven mainly by hydrophobic forces [63,64].…”
Section: Simulations Of Ternary Cp/membrane/water Systemsmentioning
confidence: 63%
“…Some previous simulation studies (e.g., [2,17]) have suggested that disaccharide molecules tend to stabilize the structure of the phospholipids bilayer since they bridge adjacent lipid head groups and preserve the membrane under cooling conditions without affecting its structure. The precipitation phenomenon renders this process effective due to the enhancement of the contact between the cell membrane and a large concentration of disaccharide molecules.…”
Section: <Formation Process Of Fine Particles During Freezing>mentioning
confidence: 99%
“…37,43 It has been long known that the molecular dynamic (MD) simulations are well suited for detailed analysis of the interaction between lipid bilayers and various chemicals and there are some recent studies reporting on the interaction between lipid bilayers and small nonwater polar molecules. [1][2][3][4][5][6][7]10,12,[17][18][19]21,22,[27][28][29][30][31][32]36,[39][40][41][42][43][44]46 Clearly, a detailed description of these studies is beyond the scope of this communication. Of direct relevance to the current study, Patra et al 30 reported the structural changes of dipalmitoylphosphatidylcholine (DPPC) lipid membranes in the presence of relatively small molar fractions (below 1.0 mol%) of ethanol and methanol in water.…”
Section: Introductionmentioning
confidence: 99%